2021
DOI: 10.1002/jcop.22478
|View full text |Cite
|
Sign up to set email alerts
|

A pilot evaluation of the Building Early Emotional Skills (BEES) curriculum in face‐to‐face and online formats

Abstract: The Building Early Emotional Skills (BEES) parenting program is designed to promote parent-child relationships and more optimal social-emotional development by addressing four sequentially built skills in parenting infants/toddlers: (1) building parental awareness of emotions in self and child; (2) listening and interacting sensitively; (3) identifying and labeling emotions; and (4) intentionally supporting early self-regulation skills. BEES used an 8-session format delivered in online or face-to-face platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Recent research has demonstrated that the online delivery of a parenting program for caregivers of children under the age of 3 years was as effective in demonstrating increases in knowledge, parenting skills, and self-reported supportive responses as an in-person delivery model. 20 A recent meta-analysis of technology-assisted parenting interventions for families experiencing social disadvantage with young children (<6 years) also found improvements in parenting behaviour and child behaviour from pre- to post-intervention. 21 While online adaptations are promising, it is unknown whether the MTC online program will lead to changes in caregiver attitudes, sense of self-competence, and caregiver stress when being delivered virtually similar in magnitude to the in-person delivery method.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that the online delivery of a parenting program for caregivers of children under the age of 3 years was as effective in demonstrating increases in knowledge, parenting skills, and self-reported supportive responses as an in-person delivery model. 20 A recent meta-analysis of technology-assisted parenting interventions for families experiencing social disadvantage with young children (<6 years) also found improvements in parenting behaviour and child behaviour from pre- to post-intervention. 21 While online adaptations are promising, it is unknown whether the MTC online program will lead to changes in caregiver attitudes, sense of self-competence, and caregiver stress when being delivered virtually similar in magnitude to the in-person delivery method.…”
Section: Introductionmentioning
confidence: 99%